Establishment of a mouse intrauterine adhesion model via transvaginal mechanical injury guided by abdominal ultrasound - Xuan Liu; Panpan Yuan; Xindi Zhang; Xin Liu; Caixiang Li; Hui Zhao; Yinci Zhang; Fan Li; Ping Zhou (PLoS ONE, 2026)
Objective To establish a clinically relevant mouse model of intrauterine adhesion (IUA) using a minimally invasive approach that combines real-time ultrasound guidance with controlled transvaginal mechanical injury. Methods Forty female C57 mice in estrus were randomly assigned to four groups (n = 10 each): ultrasound-guided transvaginal mechanical injury, laparotomy mechanical injury, absolute ethanol, and laparotomy control. Fourteen days after surgery, mice were euthanized and uterine tissue was collected for histological evaluation. Hematoxylin–eosin staining was used to assess endometrial morphology and quantify gland density, while Masson trichrome staining was used to fibrosis. Early and late experimental complications were monitored throughout the study. Results The ultrasound-guided transvaginal mechanical injury, laparotomy mechanical injury, and absolute ethanol groups displayed characteristic IUA features, including disrupted endometrial architecture, reduced gland numbers, and significantly increased fibrotic areas compared with controls (P < 0.05). Among the intervention groups, the ultrasound-guided transvaginal group showed the lowest incidence of both early and late complications. Conclusion Ultrasound-guided transvaginal mechanical injury successfully established a mouse model of IUA. This approach avoids peritoneal and full-thickness uterine damage, is safe, produces few complications, and partially mimics key aspects of the mechanical injury associated with clinical IUA, providing a reliable platform for future pathogenesis and therapeutic studies.